Effect of different chlorhexidine application times on microtensile bond strength to dentin in Class I cavities - Hyun-Jung Kang; Ho-Jin Moon; Dong-Hoon Shin (Korean Academy of Conservative Dentistry, 2012)
Objectives This study evaluated the effect of 2% chlorhexidine digluconate (CHX) with different application times on microtensile bonds strength (MTBS) to dentin in class I cavities and intended to search for ideal application time for a simplified bonding protocol. Materials and Methods Flat dentinal surfaces with class I cavities (4 mm × 4 mm × 2 mm) in 40 molar teeth were bonded with etch-and-rinse adhesive system, Adper Single Bond 2 (3M ESPE) after: (1) etching only as a control group; (2) etching + CHX 5 sec + rinsing; (3) etching + CHX 15 sec + rinsing; (4) etching + CHX 30 sec + rinsing; and (5) etching + CHX 60 sec + rinsing. Resin composite was built-up with Z-250 (3M ESPE) using a bulk method and polymerized for 40 sec. For each condition, half of the specimens were immediately submitted to MTBS test and the rest of them were assigned to thermocycling of 10,000 cycles between 5℃ and 55℃ before testing. The data were analyzed using two-way ANOVA, at a significance level of 95%. Results There was no significant difference in bond strength between CHX pre-treated group and control group at the immediate testing period. After thermocycling, all groups showed reduced bond strength irrespective of the CHX use. However, groups treated with CHX maintained significantly higher MTBS than control group (p < 0.05). In addition, CHX application time did not have any significant influence on the bond strength among groups treated with CHX. Conclusion Application of 2% CHX for a short time period (5 sec) after etching with 37% phosphoric acid may be sufficient to preserve dentin bond strength.